Developments in seasonal Atlantic basin tropical cyclone prediction - Klotzbach, Philip J., author; Schubert, Wayne, advisor; Gray, William M., committee member; Pielke, Roger, Sr., committee member; Mielke, Paul, committee member (Colorado State University. Libraries, 2007)
Seasonal forecasts of Atlantic basin hurricane activity have been issued since 1984 by the Tropical Meteorology Project at Colorado State University headed by William Gray. Since these initial forecasts were developed, considerable improvements in data and statistical techniques have led to improved amounts of skill in both hindcasting and forecasting of seasonal Atlantic basin hurricane activity. Statistical seasonal forecasts derive their skill from atmospheric and oceanic predictors that span various portions of the globe. Recent developments in statistical prediction include revised statistical predictions of tropical cyclone activity for seasonal forecasts issued in early December, early April, early June and early August. In addition, individual forecast schemes for predicting activity during the months of August, September and October have been developed. The development of landfall probabilities has been a primary area of interest over the past several years. Landfall probabilities are now available online for all United States coastal counties from Brownsville, Texas to Eastport, Maine. Atlantic basin tropical cyclone activity has been observed to increase dramatically over the past decade. Potential increases in global tropical cyclone activity as well as Atlantic tropical cyclone activity are investigated, to determine if it is possible to see a human-induced fingerprint on global or Atlantic tropical cyclone activity trends. A potential linkage between the Atlantic thermohaline circulation and Atlantic basin multidecadal variability is proposed.
Keywords: oceanography; atmosphere; physical oceanography; atmospheric sciences